Addition of Docetaxel and/or Zoledronic Acid to Standard of Care for Hormone-naive Prostate Cancer: A Cost-effectiveness Analysis. Issue 4 (July 2017) - Zhang, Pengfei; Wen, Feng; Fu, Ping; Yang, Yu; Li, Qiu
Background: The effectiveness of the addition of docetaxel and/or zoledronic acid to the standard of care (SOC) for hormone-naive prostate cancer has been evaluated in the STAMPEDE trial. The object of the present analysis was to evaluate the cost-effectiveness of these treatment options in the treatment of advanced hormone-naive prostate cancer in China. Methods: A cost-effectiveness analysis using a Markov model was carried out from the Chinese societal perspective. The efficacy data were obtained from the STAMPEDE trial and health utilities were derived from previous studies. Transition probabilities were calculated based on the survival in each group. The primary endpoint in the analysis was the incremental cost-effectiveness ratio (ICER), and model uncertainties were explored by 1-way sensitivity analysis and probabilistic sensitivity analysis. Results: SOC alone generated an effectiveness of 2.65 quality-adjusted life years (QALYs) at a lifetime cost of 20, 969.23. At a cost of 25, 001.34, SOC plus zoledronic acid was associated with 2.69 QALYs, resulting in an ICER of 100, 802.75/QALY compared with SOC alone. SOC plus docetaxel gained an effectiveness of 2.85 QALYs at a cost of 28, 764.66, while the effectiveness and cost data in the SOC plus zoledronic acid/docetaxel group were 2.78 QALYs and 32, 640.95. Conclusions: Based on the results of the analysis, SOC plus zoledronic acid, SOC plus docetaxel, and SOC plus zoledronic acid/docetaxel are unlikely to be cost-effective options in patients with advanced hormone-naive prostate cancer compared with SOC alone.